Patterns of Genetic Diversity Within Three California Quail Species Are Best Explained by Climate and Landscape Changes - Phred M. Benham; Carla Cicero; Michelle M. Davila; Erik D. Enbody; Katherine S. Miller; Allison J. Shultz; Lydia L. Smith; Michael W. Nachman; Rauri C. K. Bowie (Molecular Ecology, 2025)
Many North American game animals experienced severe population declines during the 19th century due to market hunting. However, estimates of the timing and magnitude of these declines often rely on anecdotal evidence, which makes it difficult to understand the lasting impacts of hunting pressures versus climate or landscape changes on the genetic diversity of contemporary populations. Historical reports suggest the California quail ( Callipepla californica ) suffered more significant hunting pressure in the late 19th century relative to either Gambel's ( Callipepla gambelii ) or mountain quail ( Oreortyx pictus ). Genomic data can help illuminate the extent to which historical exploitation moulded the genetic health of modern quail populations. We compared whole genome sequences from these three quail species to evaluate whether reported differences in hunting pressure affected contemporary patterns of genetic diversity. Contrary to our expectations, California quail did not exhibit any evidence for population declines until the late 20th century, long after the era of market hunting ended. California quail also exhibited the highest levels of genetic diversity across most analyses with evidence for population expansion over the past 500,000 years. In contrast, the mountain quail exhibited a long‐term population decline beginning in the middle of the last ice age 30–40 thousand years ago. The Gambel's quail appears to have suffered a more recent bottleneck in association with a major drought that impacted the desert southwest during the mid‐20th century. Gambel's quail also exhibited increased realised genetic load for mild and moderately deleterious genetic variants. Together, our results demonstrate that market hunting had little lasting impact on the genetic diversity of these quail species, whereas landscape and climate changes have led to fluctuations in effective population size ( Ne ) and the buildup of genetic load.

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Lessons for conservation from beneath the pavement - Alexis M. Mychajliw; Elizabeth R. Ellwood; Peter S. Alagona; R. Scott Anderson; Mairin A. Balisi; Eric Biber; Justin L. Brown; Jessie George; Austin J. W. Hendy; Lila Higgins; Courtney A. Hofman; Ashley Leger; et al. (Conservation Biology, 2022)

Genomic footprints of adaptation in a cooperatively breeding tropical bird across a vegetation gradient - Flavia Termignoni‐García; Juan P. Jaramillo‐Correa; Juan Chablé‐Santos; Mark Liu; Allison J. Shultz; Scott V. Edwards; Patricia Escalante‐Pliego (Molecular Ecology, 2017)
Identifying the genetic basis of phenotypic variation and its relationship with the environment is key to understanding how local adaptations evolve. Such patterns are especially interesting among populations distributed across habitat gradients, where genetic structure can be driven by isolation by distance ( IBD ) and/or isolation by environment ( IBE ). Here, we used variation in ~1,600 high‐quality SNP s derived from paired‐end sequencing of double‐digest restriction site‐associated DNA (dd RAD ‐Seq) to test hypotheses related to IBD and IBE in the Yucatan jay ( Cyanocorax yucatanicus) , a tropical bird endemic to the Yucatán Peninsula. This peninsula is characterized by a precipitation and vegetation gradient—from dry to evergreen tropical forests—that is associated with morphological variation in this species. We found a moderate level of nucleotide diversity (π = .008) and little evidence for genetic differentiation among vegetation types. Analyses of neutral and putatively adaptive SNP s (identified by complementary genome‐scan approaches) indicate that IBD is the most reliable explanation to account for frequency distribution of the former, while IBE has to be invoked to explain those of the later. These results suggest that selective factors acting along a vegetation gradient can promote local adaptation in the presence of gene flow in a vagile, nonmigratory and geographically restricted species. The putative candidate SNP s identified here are located within or linked to a variety of genes that represent ideal targets for future genomic surveys.